2012
DOI: 10.1002/jsfa.5908
|View full text |Cite
|
Sign up to set email alerts
|

Development of event‐specific PCR detection methods for genetically modified tomato Huafan No. 1

Abstract: Our results suggest that the developed event-specific PCR methods can be routinely used for identification and quantification of GM Huafan No. 1 tomato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In GM component detection, the LOD is a crucial parameter that must be determined. According to literature reports, the LOD for conventional PCR is generally around 20 copies, while for qPCR, it is around 10 copies [25,26]. The LOD of the detection system established in this study is consistent with the reported results.…”
Section: Discussionsupporting
confidence: 91%
“…In GM component detection, the LOD is a crucial parameter that must be determined. According to literature reports, the LOD for conventional PCR is generally around 20 copies, while for qPCR, it is around 10 copies [25,26]. The LOD of the detection system established in this study is consistent with the reported results.…”
Section: Discussionsupporting
confidence: 91%
“…The qPCR method has the advantages of real-time analysis, high sensitivity, less time consumption, and detection of low levels of gene-edited components. Thus, the combination of the two methods in a complementary assay could yield accurate and rapid detection [28], It will also provide some technical support to establish a detection and identification system of gene-edited foods in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification efficiency was calculated according to the slope of the standard curve: E = 10 −1/slope −1. The quantitative detection of gene editing exogenous components requires the slope of the standard curve to be in the range of −3.6 ≤ slope ≤ −3.1, which implies that the amplification efficiency is 90-110%, and the correlation coefficient (R 2 ) is ≥0.98 [28]. The results showed that the slope of Cas12-real-1 was −3.340, the amplification efficiency E was 99.3%, and the correlation coefficient R 2 was 1.…”
Section: Primer Design and Screening For Qpcrmentioning
confidence: 99%
“…Cry1Ac transgene insertion sites in tomato genome were determined using thermal asymmetric interlaced polymerase chain reaction (TAIL-PCR) in four selected transgenic lines (T 1 -18, T 1 -20, T 1 -22, T 1 -25). Five arbitrary primers (ad1, ad2, ad3, ad20 and w4) (Yang et al 2013) were tested with three Cry1Ac gene-specific sequential nested primers for amplifying the 5′ upstream (Cry1Ac51, Cry1Ac52, Cry1Ac53) and 3′ downstream regions (Cry1Ac31, Cry1Ac32, Cry1Ac33). A three step sequential PCR method was used for TAIL-PCR.…”
Section: Tail-pcr Determination Of Cry1ac Transgene Insertion Sitementioning
confidence: 99%